COVID-19 Vaccine Hesitancy and Uptake among Minority Populations in Tennessee - Donald J. Alcendor; Patricia Matthews-Juarez; Neely Williams; Derek Wilus; Mohammad Tabatabai; Esarrah Hopkins; Kirstyn George; Ashley H. Leon; Rafael Santiago; Arthur Lee; Duane Smoot; James E. K. Hildreth; et al. (Vaccines, 2023)
COVID-19 vaccine hesitancy and uptake among Southern states in the US has been problematic throughout the pandemic. To characterize COVID-19 vaccine hesitancy and uptake among medically underserved communities in Tennessee. We surveyed 1482 individuals targeting minority communities in Tennessee from 2 October 2021 to 22 June 2022. Participants who indicated that they did not plan to receive or were unsure whether to receive the COVID-19 vaccine were considered vaccine-hesitant. Among participants, 79% had been vaccinated, with roughly 5.4% not likely at all to be vaccinated in the next three months from the date that the survey was conducted. When focusing particularly on Black/AA people and white people, our survey results revealed a significant association between race (Black/AA, white, or people of mixed Black/white ancestry) and vaccination status (vaccinated or unvaccinated) (p-value = 0.013). Approximately 79.1% of all participants received at least one dose of a COVID-19 vaccine. Individuals who were concerned with personal/family/community safety and/or wanted a return to normalcy were less likely to be hesitant. The study found that the major reasons cited for refusing the COVID-19 vaccines were distrust in vaccine safety, concerns about side effects, fear of needles, and vaccine efficacy.